Sustainability of accelerated rice production in Bangladesh: Technological issues and the environment (Bangladesh Journal of Agricultural Research, 2009)
Key Words: Sustainabiity, ecosystems, yield, urbanization, soil degradation. DOI: 10.3329/bjar.v34i3.3979 Bangladesh J. Agril. Res. 34(3) : 523-529, September 2009